Neural signatures of flattened emotional experience in patients with early multiple sclerosis: a bayesian approach - Wüstenberg, Torsten; Gieß, René; Bellmann-Strobl, Judith; Kunte, Hagen; Paul, Friedemann; Hälbig, Thomas D. (Brain and behavior, 2025)
Background There is evidence that the processing of emotional information (EP) is altered in subjects with multiple sclerosis (MS). In a previous study, we found flattened emotional experience inpatients with early MS (clinically isolated syndrome and early relapsing/remitting MS) during the perception of emotional visual stimuli. The neural underpinnings of this finding are widely unknown. Objective To investigate EP-related brain mechanisms in patients with early MS and healthy controls (HC). Methods Sixteen patients without neuropsychological deficits and sixteen matched HCs were presented with pictures with negative, positive, or neutral content while performing functional magnetic resonance brain scanning. Participants rated the induced emotion regarding valence and arousal using nine-level Likert scales. Group differences and similarities in image category and valence/arousal associated brain responses and functional connectivity were assessed using Bayesian repeated measures analyses of covariance. Results Patients reported less intense emotional experience of negative and positive emotional pictures. When presented with negative pictures, (1) brain response (BR) amplitudes were found to be increased in the dorsolateral prefrontal cortex (DLPFC) and middle temporal regions, including the amygdala and (2) functional connectivity (FC) between right amygdala and orbito-frontal, ventromedial frontal, and ventral temporal regions was increased in patients with MS. Conclusion Our findings of increased FC and BR in DLPFC and amygdala in MS patients with flattened emotional experience point to a disease-related adaptive upregulation of the EP network. The latter is interpreted as emotion regulation of heightened sensitivity of amygdala activity to negative emotional content via increased fronto-temporal functional connectivity.
Zuerst veröffentlicht: 29. Oktober 2025
Gesehen am 10.12.2025